2018
DOI: 10.1136/bmjqs-2018-007976
|View full text |Cite
|
Sign up to set email alerts
|

Effects and costs of implementing predictive risk stratification in primary care: a randomised stepped wedge trial

Abstract: AimWe evaluated the introduction of a predictive risk stratification model (PRISM) into primary care. Contemporaneously National Health Service (NHS) Wales introduced Quality and Outcomes Framework payments to general practices to focus care on those at highest risk of emergency admission to hospital. The aim of this study was to evaluate the costs and effects of introducing PRISM into primary care.MethodsRandomised stepped wedge trial with 32 general practices in one Welsh health board. The intervention compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 18 publications
1
28
0
Order By: Relevance
“…The vast majority of published clinical prediction models are never used in clinical practice 19. One reason for this is the lack of a specific clinical decision making process that the model could meaningfully inform or optimise; simply predicting future events on their own might not help a clinician do anything differently20 (in other words: just because we can, it does not mean we should). This is an important departure from the lone wolf attitude, which has helped foster innovation over the past few decades in ML/AI for health.…”
Section: Critical Questionsmentioning
confidence: 99%
“…The vast majority of published clinical prediction models are never used in clinical practice 19. One reason for this is the lack of a specific clinical decision making process that the model could meaningfully inform or optimise; simply predicting future events on their own might not help a clinician do anything differently20 (in other words: just because we can, it does not mean we should). This is an important departure from the lone wolf attitude, which has helped foster innovation over the past few decades in ML/AI for health.…”
Section: Critical Questionsmentioning
confidence: 99%
“…32 The findings justified the cautious approach, as the intervention was shown to be ineffective and resulted in increased costs, emergency admissions, and bed days. 13,32 Further studies published after the widespread roll out of EARS, including a systematic review of case management for at-risk individuals (not necessarily identified through EARS tools), and an observational study of multidisciplinary case management for risk stratified patients, found increased costs and health service use. 15,33 It is far from uncommon for health innovations to be introduced at scale and great cost without an understanding of their costs and effects.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Of the studies that use EARS to select patients for community interventions (typically case management or virtual wards), none reported reductions in admissions, cost savings, or significant patient benefit. [13][14][15][16] Although there is no strong evidence supporting the clinical or cost effectiveness of interventions incorporating EARS tools, there has been concerted political and practical investment in EARS across the developed world. [17][18][19] In the UK, state funding supported the development of risk models: Patients at Risk of Readmission (PARR) and the Combined Model in England; Scottish Patients at Risk of Readmission and Admission (SPARRA) in Scotland; and Predictive Risk Stratification Model (PRISM) in Wales.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in 2018, Persell and colleagues4 noted worse blood pressure at 12 months in a group of patients assigned to an electronic health record-based medication management tool compared with the control. Readers of BMJ Quality & Safety may also recall a 2019 study in which utilisation of a model to estimate risk of ED presentation in 32 general practices in Wales resulted in increased ED utilisation 5. The accompanying editorial reflected on a number of examples of unintended consequences of quality improvement efforts 6.…”
Section: Effect Of a Hospital-initiated Program Combining Transitionamentioning
confidence: 99%